Enterprise Risk Management, Corporate Social Responsibility, Dan Kinerja Perusahaan Manufaktur (BEI) - Santoso, Dimas; Husaini, Husaini (Penerbit Goodwood, 2025)
Purpose: This study examines the effect of Enterprise Risk Management (ERM) on the performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX), with Corporate Social Responsibility (CSR) as a mediating variable. Methodology/approach: Using panel data regression and Baron & Kenny’s (1986) mediation analysis, this study analyzed 80 firm-year observations from 2019–2023. ERM was measured based on six criteria adapted from Florio & Leoni (2017). CSR was proxied by ESG scores published by IDX, while firm performance was assessed using Return on Assets (ROA) and Tobin’s Q. Data were processed using EViews 12. Results/findings: ERM positively and significantly affects both ROA and Tobin’s Q, indicating that effective risk management enhances firm profitability and market value. However, ERM does not significantly influence CSR, and CSR negatively affects ROA and has no significant effect on Tobin’s Q. Thus, CSR does not mediate the relationship between ERM and firm performance. Conclusions: ERM improves firm performance, but has no effect on CSR. CSR does not enhance performance and fails to mediate the ERM–performance relationship. Limitations: The study does not incorporate control variables such as firm size or leverage. CSR is measured solely using ESG scores, which may not fully reflect CSR implementation. Contribution: This research contributes to the understanding of ERM’s direct impact on firm performance in emerging markets. It highlights the need for better integration between risk management and CSR strategies to generate financial and reputational benefits.